MANAJEMEN PENGATURAN JAM KERJA UNTUK MENINGKATKAN KINERJA KARYAWAN MENGGUNAKAN PENDEKATAN GENDER DI APOTEK ENGGAL SEHAT MAJENANG - Sudrajat, Bayu; Wahyuningsih, Apriliyani (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2023)
This research is related to the analysis of working hours to improve employee performance. This study aims to determine the suitability of the management of working hours for employees at the Enggal Sehat Pharmacy Majenang based on Law Number 13 of 2003 and to find out the arrangements for working hours through a gender approach. This research is a field research using a qualitative approach. The types of data used in this research are primary data and secondary data. Data collection in this study was carried out by means of interviews and data analysis using descriptive analysis. The results showed that the management of working hours arrangements for employees at the Enggal Sehat Pharmacy was not in accordance with Law Number 13 of 2003, namely that each female employee gets 7 working days and 2 days off for 1 month with a length of work of 8 hours per day. Furthermore, the form of setting working hours using a gender approach is in accordance with Law Number 13 of 2003, namely the implementation of leave which should be given to female employees.